Institutional Support for Academic Engagement in Online and Blended Learning Environments: Exploring Affective, Behavioral, and Cognitive Dimensions - Graham, Charles R.; Borup, Jered; Tuiloma, Sara; Martínez Arias, Adriana; Parra Caicedo, Diana María; Larsen, Ross (Online Learning, 2023)
In light of the disruptions caused by the COVID-19 pandemic, leaders of higher education institutions around the world have been contemplating ways to help their universities engage in a digital transformation that must have student engagement and learning as the foremost considerations. This study reports on the work conducted at a university in Colombia that created an evaluation instrument based on the Academic Communities of Engagement (ACE) framework (Borup et al., 2020) to examine how well the institution was supporting the affective, behavioral, and cognitive (ABC) dimensions of engagement in its online and blended learning course offerings. This survey, the ACE in Higher Education (ACE-HE), measures indicators of the ABC engagement dimensions as well as indicators of institutional support for those elements. The survey was completed by 1,295 university students representing a broad demographic profile. Structural equation modeling found good fit for both the model of ABC engagement dimensions and the model of institutional support for ABC engagement dimensions. Institutional support for affective engagement showed strong relationships to affective, behavioral, and cognitive indicators of engagement, while institutional support for behavioral and cognitive engagement did not have the same outcome. This research provides access to both English and Spanish versions of the ACE-HE instrument. It also highlights ideas for institutions that want to improve their support for student ABC engagement dimensions in online and blended environments. Finally, several implications for making updates to the ACE framework are shared.